MULTIPLE EULER-MACLAURIN SUMMATION FORMULA - Pogány, Tibor K. (Matematichki Bilten, 2005)
\(d\)-dimensional finite Euler-Maclaurin summation formula is derived for sequences which are restrictions of coordinatewise once differentiable nonnegative real functions.